PENGARUH LAPORAN MANAJERIAL, KUALITAS AUDIT, DAN KOMITE AUDIT TERHADAP KUALITAS PELAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - TriYulia, Nur Cahya; Alfian, Nurul (Aktiva : Jurnal Akuntansi dan Investasi, 2024)
Financial reports present the financial position and financial performance of an entity. Financial reports are accountability reports that are used by management to increase the company's value in the future by evaluating deficiencies in previous periods. The aim of this research is to analyze the influence of internal company factors, including Managerial Reports, Audit Quality and Audit Committees partially and simultaneously on the Quality of Financial Reporting of property and Real Estate companies listed on the Indonesia Stock Exchange for the period 2020 - 2023.            The partial test results from this research are that partial (individual) Managerial Reports have no effect on the quality of financial reporting, which obtained a result of 0.131. Audit quality has a significant influence on the quality of financial reporting, which obtained a result of 0.011. And the Audit Committee has a significant influence on the quality of financial reporting, which obtained a result of 0.000.